What do hospitalists experience as barriers and helpful factors for having ACP conversations? A systematic qualitative evidence synthesis. (March 2019) - Vanderhaeghen, Birgit; Van Beek, Karen; De Pril, Mieke; Bossuyt, Inge; Menten, Johan; Rober, Peter
Background: Hospitalists seem to struggle with advance care planning implementation. One strategy to help them is to understand which barriers and helpful factors they may encounter. Aims: This review aims to give an overview on what hospitalists experience as barriers and helpful factors for having advance care planning conversations. Method: A systematic synthesis of the qualitative literature was conducted. Data sources: A bibliographic search of English peer-reviewed publications in PubMed, Embase, CINAHL, Central, PsycINFO, and Web of Science was undertaken. Results: Hospitalists report lacking communication skills which lead to difficulties with exploring values and wishes of patients, dealing with emotions of patients and families and approaching the conversation about letting a patient die. Other barriers are related to different interpretations of the concept advance care planning, cultural factors, like being lost in translation, and medicolegal factors, like fearing prosecution. Furthermore, hospitalists report that decision-making is often based on irrational convictions, and it is highly personal. Physician and patient characteristics, like moral convictions, experience, and personality play a role in the decision-making process. Hospitalists report that experience and learning from more experienced colleagues is helpful. Furthermore, efficient multidisciplinary co-operation is helping. Conclusion: This systematic review shows that barriers are often related to communication issues and the convictions of the involved hospitalist. However, they seem to be preventable by creating a culture where experienced professionals can be consulted, where convictions can be questioned, and where co-operation within and between organizations is encouraged. This knowledge can serve as a basis for implementation.